2012
DOI: 10.1128/aem.07879-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Airflow and Changing Humidity on the Aerosolization of Respirable Fungal Fragments and Conidia of Botrytis cinerea

Abstract: ABSTRACTThe purpose of this study was to investigate the aerosolization of particles (micro- and macroconidia and fragments) fromBotrytis cinereacultures in relation to potential human inhalation in indoor environments. The influence of the following factors on the aerosolization ofB. cinereaparticles was studied: exposure to airflow, relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 46 publications
5
39
1
Order By: Relevance
“…Kildesø et al (2003) used a rotating air source to aerosolize and measure fungal spores grown on a gypsum board using an aerodynamic particle sizer (APS) and observed variation of fungal spore flux with fungus type. Madsen et al (2012) using a similar setup observed that spore release increased with decreasing air relative humidity. Gorny et al (2003) used a specially designed flow through chamber to measure fungal spores release from an agar surface and a ceiling tile using an optical particle counter.…”
Section: Introductionmentioning
confidence: 78%
“…Kildesø et al (2003) used a rotating air source to aerosolize and measure fungal spores grown on a gypsum board using an aerodynamic particle sizer (APS) and observed variation of fungal spore flux with fungus type. Madsen et al (2012) using a similar setup observed that spore release increased with decreasing air relative humidity. Gorny et al (2003) used a specially designed flow through chamber to measure fungal spores release from an agar surface and a ceiling tile using an optical particle counter.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, the size of fungal spores has been found to depend on the relative humidity, i.e. higher the relative humidity is, the larger the spores are (Reponen et al, 1996;Madsen, 2012). The spores of basidiomycete fungi are in general larger than those of ascomycete (Reponen et al, 2001;Manninen et al, 2014;Hussein et al, 2013;, and the basidiomycete fungi are known to sporulate mainly during autumn when the relative humidity is high (Kauserud et al, 2011).…”
Section: Overview Of Meteorological Factors and Sourcesmentioning
confidence: 99%
“…According to , the majority of the fungal DNA detected during summer and autumn is from fungal species belonging to Basidiomycota. Based on previous results , 2012, we have assumed that most the fungal DNA collected on our filters is also derived from basidiomycete fungi. Because only a few 18S rDNA regions of fungi are fully annotated, we have selected the P. radiata as a model basidiomycete fungus and calculated the gene copy numbers to fungal cells based on the assumption that all fungi in this experiment have approximately the same number of 18S rDNA gene copies as this fungus has (Kuuskeri et al, 2016).…”
Section: Dna Amplificationmentioning
confidence: 99%
“…Such parameters include the temperature and relative humidity (RH) of the air, both indoors and outdoors. In fact, the relative humidity has been shown to have profound effects on spore and particle release from fungal structures with which surfaces are infested (26,39). Denmark is located in northern Europe and experiences a temperate climate.…”
mentioning
confidence: 99%